The Compressive Behavior of 3D Weft Knitted Spacer Fabrics Designed for Cushioning Applications (Journal of Fiber Bioengineering and Informatics, 2018)
In this research work, the effect of various construction parameters and structural characteristics ofweft knitted spacer fabric on the compressive behavior and energy absorption capability was studied.The potential compression mechanism of the fabric was identified with support of the compressionstress-strain curve, work done and efficiency at different compression stages. The results show that thecompressive stress at the same compressive strain increases with the fabric density, and the stress-straincurves of spacer fabrics with different densities were all composed of initial, elastic region, plateau regionand densification region. Third order polynomial regression model was used to establish the elasticdeformation properties to obtain the compression results. The spacer fabrics ideal energy-absorptionefficiency curves were obtained from their stress-strain curves and all findings show that stresscorresponding to at the peak of the energy-absorption efficiency was closed to the densification stressof material. Advance statistical evaluation and one-way analysis of variance is used to analyze thesignificance of various factors such as thickness, spacer yarn diameter and surface structures on energyabsorption at maximum compression load and deformation. These findings are important requirementsfor designing weft knitted spacer fabrics for cushioning applications in car seats, mattress, shoe insolesetc.
Keywords: Weft Knit Spacer Fabrics; Compression Stress; Compressive Energy Absorption; Efficiency